2019
DOI: 10.1038/s41598-019-39475-w
|View full text |Cite
|
Sign up to set email alerts
|

Mixed stock analysis of juvenile green turtles aggregating at two foraging grounds in Fiji reveals major contribution from the American Samoa Management Unit

Abstract: In this study we assessed the breeding population, or Management Unit (MU), origin of green turtles ( Chelonia mydas ) present at Yadua Island and Makogai Island foraging grounds in Fiji, central South Pacific. Based on analysis of mitochondrial (mt) DNA sequences from 150 immature green turtles caught during surveys carried out in 2015–2016, we identified a total of 18 haplotypes, the most common being CmP22.1 (44%) which is a primary haplotype characterizing the American Samoa breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This decreasing trend is made more concerning because it appears relatively independent of the increasing green turtle abundance trend at nesting beaches in the North Atlantic (Seminoff et al 2015) and represents a reversal from previous trends at this same study site (Ehrhart et al 2007). Juvenile sea turtle aggregations, including the IRL, are typically mixed stocks from multiple nesting beaches (e.g., Bass and Witzell 2000, Bagley 2003, Piovano et al 2019, Stewart et al 2019), and it is therefore possible that changes at an important juvenile habitat like the IRL could eventually impact demographic trends over a geographically widespread area. However, it is also possible that changing habitat conditions at one location would have relatively little impact at broader scales.…”
Section: Discussionmentioning
confidence: 99%
“…This decreasing trend is made more concerning because it appears relatively independent of the increasing green turtle abundance trend at nesting beaches in the North Atlantic (Seminoff et al 2015) and represents a reversal from previous trends at this same study site (Ehrhart et al 2007). Juvenile sea turtle aggregations, including the IRL, are typically mixed stocks from multiple nesting beaches (e.g., Bass and Witzell 2000, Bagley 2003, Piovano et al 2019, Stewart et al 2019), and it is therefore possible that changes at an important juvenile habitat like the IRL could eventually impact demographic trends over a geographically widespread area. However, it is also possible that changing habitat conditions at one location would have relatively little impact at broader scales.…”
Section: Discussionmentioning
confidence: 99%
“…Green turtles can alter their foraging behaviour as evidenced by consumption of invasive seagrass species that spread into key foraging habitats (e.g., Becking et al 2014;Whitman et al 2019). Turtles might also expand their foraging home ranges, as they have with serial residency in Shark Bay, Western Australia (Thomson et al 2018), or they may shuttle between foraging sites (Piovano et al 2019) or even adapt to new foraging sites, as demonstrated by a loggerhead turtle that re-located to a new site after flooding and a tropical cyclone destroyed > 1000 km 2 benthic habitat in its home range (Shimada et al 2020).…”
Section: Climate Change Considerationsmentioning
confidence: 99%
“…The average level of energy of the local soundscape (86-102 dB re: 1 μPa-rms) observed at frequencies from 200 Hz to 700 Hz matched the hearing sensitivity of juvenile green turtles. Consequently, it is likely that the juvenile green turtles from different rookeries of the South Pacific and aggregating at the two Fijian islands [71] are capable of perceiving both the geophonic and biophonic components locally present.…”
Section: Discussionmentioning
confidence: 99%
“…Fieldwork was carried out in 2018 at Makogai Island and Yadua Island in Fiji ( Fig 1A ), tropical South Pacific, where juvenile green turtles from different stocks form foraging aggregations in shallow coastal waters [ 71 , 72 ]. The surface areas of Makogai and Yadua Islands are about 8 km 2 and 15 km 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%